2021
DOI: 10.1186/s12933-021-01395-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal glucose, HbA1c, glucose-HbA1c ratio and stress-hyperglycaemia ratio cut-off values for predicting 1-year mortality in diabetic and non-diabetic acute myocardial infarction patients

Abstract: Background Stress-induced hyperglycaemia at time of hospital admission has been linked to worse prognosis following acute myocardial infarction (AMI). In addition to glucose, other glucose-related indices, such as HbA1c, glucose-HbA1c ratio (GHR), and stress-hyperglycaemia ratio (SHR) are potential predictors of clinical outcomes following AMI. However, the optimal blood glucose, HbA1c, GHR, and SHR cut-off values for predicting adverse outcomes post-AMI are unknown. As such, we determined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 52 publications
(61 reference statements)
3
47
0
Order By: Relevance
“…Our findings suggest that the SHR is a better predictor of STEMI prognosis than the ABG level. Consistent with the current study, Sia et al investigated the optimal cut-off value of SHR and ABG for predicting all-cause mortality in patients with AMI who had undergone PCI and found that SHR was better than ABG, regardless of the presence or absence of DM [ 9 ]. Şimşek B et al reported that higher SHR values were associated with an increased risk of no-flow in patients with STEMI after primary PCI and suggested that there were no interactions between SHR and diabetes status [ 24 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings suggest that the SHR is a better predictor of STEMI prognosis than the ABG level. Consistent with the current study, Sia et al investigated the optimal cut-off value of SHR and ABG for predicting all-cause mortality in patients with AMI who had undergone PCI and found that SHR was better than ABG, regardless of the presence or absence of DM [ 9 ]. Şimşek B et al reported that higher SHR values were associated with an increased risk of no-flow in patients with STEMI after primary PCI and suggested that there were no interactions between SHR and diabetes status [ 24 ].…”
Section: Discussionsupporting
confidence: 80%
“…The authors reported that SHR is an effective predictor of adverse events in patient with critical illness [ 7 ]. Further studies have demonstrated that the SHR exhibits better predictive value than ABG in cases of AMI [ 8 , 9 ]. However, data regarding the effect of SHR on the prognosis of STEMI remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we observed that elevated fasting blood glucose in AMI has a strong association with worse outcomes. Previous studies have primarily focused on the prognosis value of admission hyperglycemia in both patients with and without diabetes [1][2][3][4]. Some studies showed that persisting hyperglycaemia was a more accurate and stronger independent predictor of risk than admission blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia during hospital admission is common in patients with AMI and independently associated with worse prognosis [1][2][3][4], although the association may be nonlinear [5], and data conflict as to whether this association varies by diabetes status [4,6,7]. Admission hyperglycemia occurs in 25-50% of patients, depending on the definition of admission hyperglycemia [8].…”
Section: Introductionmentioning
confidence: 99%
“…As Yang et al [ 18 ] reported, the TyG index does not accurately predict prognosis for non-diabetic CAD patients. Although, HbA1C has been used for non-diabetic patient prognosis with varying degrees of accuracy [ 30 32 ]. Which suggests there is a need to intercalate one (or more) inflammation markers into a cohesive nomogram or with larger datasets into an artificial intelligence model.…”
Section: Discussionmentioning
confidence: 99%